DILEMA PENETAPAN UMK/UMSK KABUPATEN BEKASI KAJIAN TERHADAP PERATURAN PEMERINTAH RI NOMOR 78 TAHUN 2015 TENTANG PENGUPAHAN - Mahayoni Mahayoni (President University, 2017)
For years, the determination of the Regency/City Minimum Wage or UMK and the Regency/City Sector Minimum Wage or UMSK has always caused tension to many parties. The difference in viewpoints between Labor Unions and employers' business associations always colored the long series of meetings at the Bekasi Regency Wage Council. Sometimes it is colored by demonstrations and debates that become the dynamics in making decisions that are very much awaited by workers and employers. The issuance of PP 78 in 2015 which determines with certainty the issue of UMSK does not necessarily solve the problem. Although the Workers/Laborers rejected this PP, all of them respected the new rules. It's not fun for all parties, but at least there is certainty about the amount of UMK every year. However, the determination of UMSK is even more confusing. The leading sector studies that form the basis of the Depekab proposal to Workers/Labor associations and Employers' associations in the sector did not satisfy all parties. Each of them tries to propose each other's studies and rejects the other's studies. The Government elements in the Depekab who are facilitators have tried to conduct studies by forming an independent team and involving Labor unions and Employers' associations, but the results have not been accepted by the two elements. This means that the completion of the UMSK determination will still face a steep road. However, Indonesian culture that always upholds deliberation and consensus is so prominent. The end of all studies is the agreement between the Labor association and the Employers' association in the sector that will be superior is the key.